The first record of Ia io Thomas, 1902 (Mammalia: Chiroptera: Vespertilionidae) from the Sundaic Subregion, with a description of a new subspecies from peninsular Thailand - Soisook, Pipat; Sribuarod, Kriangsak; Karapan, Sunate; Safoowong, Mongkol; Billasoy, Sawwalak; Thong, Vu Dinh; Chang, Yang; Gong, Lixin; Lin, Aiqing; Sztencel-Jabłonka, Anna; Bogdanowicz, Wiesław; Bates, Paul J. J. (Zootaxa, 2017)
The Great evening bat Ia io Thomas, 1902, previously considered as an endemic to the Indochinese subregion, is reported from the Sundaic subregion for the first time based on specimens collected from three localities in Surat Thani Province and Phang Nga Province, peninsular Thailand. It is described herein as a new subspecies based on its substantially larger body and skull size. The mitochondrial COI and cytochrome b genes reveal that the new subspecies has a genetic distance of 1.89% and 1.65%, respectively, from the nominate subspecies. Echolocation calls comprise four harmonics, with the maximum energy in the first harmonic (fmaxe) of 23.6–27.4 kHz. Notes on the population size as well as roosting and foraging behaviour are also provided.